Informed entry in auctions (2018)
We examine entry decisions in first-price and English clock auctions with participation costs. Potential bidders observe their value and report maximum willingness to pay (WTP) to participate. Entry occurs if revealed WTP (weakly) exceeds the randomly drawn participation cost. We find no difference in WTP between auction formats, although males have a higher WTP for first-price auctions. WTP is decreasing in the number of potential bidders, but this reduction is less than predicted and small in magnitude. © 2017, Springer-Verlag GmbH Germany.